MELHOR STUDENT WELL-BEING: : AN ANALYTICAL MODEL FOR STUDENT ASSISTANCE'S RESEARCHES IN BRAZIL (Interdisciplinary Studies Journal, 2026)
This article proposes an analytical model to examine the National Student Assistance Policy (PNAES) from the perspective of well-being. It highlights the institutionalization of Student Assistance (AE) from its creation as the National Student Assistance Program (2007) to its consolidation as a National Policy in 2024 by Law 14.914. This affirmative action policy aims to promote equity by ensuring socioeconomically disadvantaged students the conditions to regularly pursue their undergraduate studies. It aims to improve student academic performance by reducing retention and dropout rates. To this end, it meets the material conditions for students' continued attendance at federal higher education institutions, including housing, food, transportation, digital inclusion, and daycare. However, to foster well-being, it is also necessary to incorporate non-material dimensions into the analytical model of its evaluations that meet the needs of identity, belonging, and sociability of the beneficiaries of this public policy.
Keywords: National Student Assistance Policy; Well-being; Higher Education; Public Policy